Biotyping and PCR Based Detection of Staphylococcus Aureus in Mastitic Large Ruminant Population of District Faisalabad - Ashfaq, Khurram; Muhammad, Ghulam; Yousaf, Arfan; Khan, Sultan Habibullah; Sajjad ur Rehman (Indus Journal of Bioscience Research, 2024)
S. aureus is considered one of the most important economical disease of dairy enterprise worldwide which affect the quantity and quality of the milk. The present study aimed at detection of S. aureus in mastitic cows and buffaloes using PCR based and biotyping techniques. For this purpose, a total of 374 lactating animals (cows n= 169; buffaloes n= 205) belonging to five small holder and three institutional dairy herds were examined for clinical and subclinical mastitis. Using Surf Field Mastitis Test (SFMT), 14 (8.28%) out of 169 cows and 35(17.07%) out of 205 buffaloes were clinically mastitic while 157 (23.22%) out of 676 were apparently mastitis free quarters. While 205 buffaloes were found positive for subclinical mastitis. Biotyping with the aid of Staphytect plusTM kit, 83 of the recovered isolates of S. aureus were assigned to six patterns. Predominant pattern embraced 28, 17, 15, 9, 7 and 7 of pattern I, IV, III, V, II and VI, respectively showing fairly strong biotype herd association. From these 83 biotypes, coagulase gene was confirmed in 79 isolates. It was hence concluded that coagulase gene primer PCR was found to be the most efficient and sensitive diagnostic technique for detection and identification of clinical and subclinical mastitis.